Serum Gastrin and the Antral Mucosa in Atrophic Gastritis. Issue 5785 (20th November 1971) - Strickland, R. G.; Bhathal, P. S.; Korman, M. G.; Hansky, J.
Abstract : The gastric antral mucosa was studied histologically in 22 patients with atrophic gastritis, of whom 11 had high levels and 11 had normal levels of serum gastrin. The antrum was graded histologically from normal to grade 3 gastritis. All patients with hypergastrinaemia (nine seropositive and two seronegative for parietal cell antibody) had either a normal antrum or minimal (grade 1) antral gastritis. In contrast all but one patient without raised serum gastrin (nine seronegative and two seropositive for parietal cell antibody) had severe (grades 2-3) antral gastritis. Thus circulating gastrin levels observed in patients with gastritis and achlorhydria can be directly related to the presence or absence of antral mucosal damage. Comparison of the histological appearances of the antral mucosa with serum gastrin and parietal cell antibody status has provided a basis for the separation of two distinctive forms of atrophic gastritis.